Building Flexibility into Commonwealth Tax Legislation: A Case for the Use of an Extra Statutory Concession Power - Wilson-Rogers, Nicole (Lawbook Co., 2013)
This article examines the advantages and disadvantages of utilising an extra statutory concession power (ESCP) in Australia's Commonwealth tax legislation and suggests the key components for establishing a statutory ESCP. The debate regarding the use of ESCPs raises fundamental issues regarding the use of discretion within a revenue Act, the amout of discretionary power that should be vested in an administrator and the issues an ESCP presents in relation to the rule of law.